Japan Nuclear Human Resource Development Network. (September 2017) - Fujiwara, Kentaro
Abstract: The "Japan Nuclear Human Resource Development Network (JN-HRD Network)" was established in November 2010. It is a framework for nuclear HRD, consisting of the industry, the academia, and the government of Japan, to share information and to promote national HRD activities in a harmonized, integrated and strategic manner. 73 organizations are members of the JN-HRD Network at present. The HRD Roadmap was created by the JN-HRD Network in 2014, and the JN-HRD has performed various activities to achieve the common goal since its establishment.